Exploring aquaporin functions during changes in leaf water potential - Byrt, Caitlin S.; Zhang, Rose Y.; Magrath, Isobel; Chan, Kai Xun; De Rosa, Annamaria; McGaughey, Samantha (Frontiers in Plant Science, 2023)
Maintenance of optimal leaf tissue humidity is important for plant productivity and food security. Leaf humidity is influenced by soil and atmospheric water availability, by transpiration and by the coordination of water flux across cell membranes throughout the plant. Flux of water and solutes across plant cell membranes is influenced by the function of aquaporin proteins. Plants have numerous aquaporin proteins required for a multitude of physiological roles in various plant tissues and the membrane flux contribution of each aquaporin can be regulated by changes in protein abundance, gating, localisation, post-translational modifications, protein:protein interactions and aquaporin stoichiometry. Resolving which aquaporins are candidates for influencing leaf humidity and determining how their regulation impacts changes in leaf cell solute flux and leaf cavity humidity is challenging. This challenge involves resolving the dynamics of the cell membrane aquaporin abundance, aquaporin sub-cellular localisation and location-specific post-translational regulation of aquaporins in membranes of leaf cells during plant responses to changes in water availability and determining the influence of cell signalling on aquaporin permeability to a range of relevant solutes, as well as determining aquaporin influence on cell signalling. Here we review recent developments, current challenges and suggest open opportunities for assessing the role of aquaporins in leaf substomatal cavity humidity regulation.